The Role of Islamic Religious Education Teachers in Forming Student Discipline at Elementary School 01 Bumi Sari - Widyawati, Intan Wahyu; Setiawan, Dedi; Arifin, M. Zainal (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
Student discipline is an important aspect in the world of education that contributes to academic success and character formation. This research aims to analyze the role of Islamic Religious Education (PAI) teachers in forming student discipline at SDN 01 Bumi Sari. The research method used is a qualitative approach with data collection techniques in the form of observation, interviews and documentation. The research results show that PAI teachers have a significant role in forming student discipline through example, habituation, and consistent application of rules. Factors that support the successful formation of student discipline include the teacher's active role in providing motivation, collaboration with parents, and the application of learning methods that instill disciplinary values. However, there are also challenges faced, such as students' lack of awareness of the importance of discipline and minimal parental involvement in monitoring children's behavior at home. Thus, it is hoped that this research can provide insight for teachers, parents and schools in improving student discipline through a more optimal role of PAI teachers.